Effects of different types of Trichoderma formulations on pineapple (Ananas comosus) cv. MD2 growth performance, plant nutrients and Trichoderma availability / Norsyafiqah Jaafar - Jaafar, Norsyafiqah (2021)
An increasing demand for pineapple cv. MD2 has led to the intensification of the crop cultivation. A field study was conducted to determine the effects of different carriers of Trichoderma formulations on growth performance; concentration and nutrient content status and inoculant availability in soil. Treatments were applied before planting with T1 (Trichoderma+molasses), T2 (Trichoderma+molasses+compost) and T3 (uninoculated plant). Chemical fertilizers was applied as recommended by MPIB. Plant (D leaf) and soil analysis were determined using the D leaf samples at 16, 24 and 64 weeks after planting (WAP). Combination of Trichoderma with both molasses and compost produced the highest average total dry mass production of pineapple (1107.85g), followed by Trichoderma with molasses (1016.04g) and control (975.32g) during final harvesting. Dry mass of D leaf also showed significant difference of plant treated with Trichoderma (T1 - 22.3g and T2 - 25.7g) with control (15.9g). T2 produced the highest amount of dry mass production for each plant part compared to T1 and T3. Application of both treatment with Trichoderma produced highest average plant height with respectively 56cm at 20WAP. The highest number of leaves and stem diameter were recorded from T1; obtained 35 leaves and 63cm diameter respectively. No significant difference observed in yield production (fruit fresh weight) and total soluble sugars. T2 produced the highest average fruit weight and total soluble sugars (2.35kg & 16.53 0brix) followed by T1 (2.24kg & 16.12 0brix ) and T3 (2.04kg & 16.10 0brix). Similar trend was observed in N concentration of pineapple D leaf and root. T2 recorded the highest N concentration in both D leaf and root (1.62% & 0.64%) followed by T1 (1.52% & 0.63%) and T3 (1.36% & 0.54%). The incorporation of Trichoderma with molasses and compost gained more inoculant population compared to the single-use molasses. Present study indicated that combination of Trichoderma with molasses and compost produced better growth performance, enhanced plant nutrient concentration and produced more inoculant population in soil for pineapple cv. MD2. Therefore, the study suggested that the combination of both molasses and compost with Trichoderma spp. can be used by farmers for gaining good quality of pineapple cv. MD2.